2017
DOI: 10.4172/2155-6105.1000313
|View full text |Cite
|
Sign up to set email alerts
|

Socio Demographic Correlates of Depressed Patients Attending a Tertiary Hospital in Nigeria

Abstract: Objective: To identify the socio-demographic factors that correlate with depression in patients attending a tertiary hospital in the Niger Delta region of Nigeria.Methods: 470 subjects, recruited by a systematic sampling method participated in the study. The Beck's Depression Inventory (BDI) was administered to each person. Only one hundred and eighty five subjects met the criteria for the second stage of the study, (a score of 18 and above on the BDI). Diagnosis was made with the Composite International Diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The married subjects were higher in depression with suicidal behaviour group (68%) than depression without suicidal behaviour (64%) groups. 18 It was found that being married might have protective effect on suicidal behaviour due to better social and interpersonal support. The depression with suicidal behaviour group had higher preponderance of (76%) Hindu subjects which is in agreement of the local geographical distribution of the religion.…”
Section: Discussionmentioning
confidence: 99%
“…The married subjects were higher in depression with suicidal behaviour group (68%) than depression without suicidal behaviour (64%) groups. 18 It was found that being married might have protective effect on suicidal behaviour due to better social and interpersonal support. The depression with suicidal behaviour group had higher preponderance of (76%) Hindu subjects which is in agreement of the local geographical distribution of the religion.…”
Section: Discussionmentioning
confidence: 99%